Fish diversity of Kamala River, Siraha, Nepal - Kumar, Prakash (Nepalese Journal of Biosciences, 2016)
Eighty one species of fish spread over 17 families and 44 genera were collected during September 2015 to August 2016 from the Kamala River, Nepal. Cyprinidae family was represented by 41 species and Labeo was the largest genus.